Novel insights into the intraepithelial spread of extrahepatic cholangiocarcinoma: clinicopathological study of 382 cases on extrahepatic cholangiocarcinoma - Nagashima, Daisuke; Esaki, Minoru; Nara, Satoshi; Ban, Daisuke; Takamoto, Takeshi; Mizui, Takahiro; Shimada, Kazuaki; Hiraoka, Nobuyoshi (Frontiers in Oncology, 2023)
Background: Extrahepatic cholangiocarcinoma (eCCA) is a rare and aggressive disease, and consisted of conventional eCCA and intraductal papillary neoplasm of the bile duct (IPNB). Intraepithelial spread (IES) of cancer cells beyond the invasive area is often observed in IPNBs; however, the prevalence of IES remains to be examined in conventional eCCAs. Here, we evaluated the clinicopathological features of eCCAs according to tumor location, with a focus on the presence of IES. The IES extension was also compared among biliary tract cancers (BTCs). Methods: We examined the prevalence and clinicopathological significance of IES in eCCAs (n=382) and the IES extension of BTCs, including gallbladder (n=172), cystic duct (n=20), and ampullary cancers (n=102). Results: Among the invasive eCCAs, IPNB had a higher rate of IES (89.2 %) than conventional eCCAs (57.0 %). Among conventional eCCAs, distal eCCAs (75.4%) had a significantly higher prevalence of IES than perihilar eCCAs (41.3%). The presence of IES was associated with a significantly higher survival rate in patients with distal eCCAs (P=0.030). Extension of the IES into the cystic duct (CyD) in distal eCCAs that cancer cells reached the junction of the CyD was a favorable prognostic factor (P<0.001). The association of survival with IES, either on the extrahepatic bile duct or on the CyD, differed depending on the tumor location and type of eCCA. The extension properties of IES were also dependent on different types of tumors among BTCs; usually, the IES incidence became higher than 50% in the tissues that the tumor developed, whereas IES extension to other tissues decreased the incidence. Conclusion: Thus, eCCAs have different clinicopathological characteristics depending on the tumor location and type.